2022
DOI: 10.1021/acs.macromol.2c01123
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Dependence of Contact Angles in Multilayered Ultrathin Polymer Films

Abstract: The wetting behavior of ultrathin polymer films (<100 nm) is systematically studied via dynamic contact angle measurements on a model bilayer system of cross-linked polystyrene (PS) and poly­(methyl methacrylate) (PMMA) to deconvolute surface energy contributions from material property changes due to confinement and long-range influence from underlayers, i.e., wetting transparency. We find that ultrathin PMMA films show no detectable material property changes and block the influence from PS underlayers when su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 67 publications
1
18
0
Order By: Relevance
“…[74] It is also reported that T g -confinement effects are pronounced in crosslinked systems when compared to analogous linear polymers. [92] These pronounced effects in the crosslinked system support the large critical thicknesses for contact angle dependence on crosslinked ultrathin PS/PMMA films observed by Petek et al [36] This review invites future work to combine the additive vdW potential with the cooperative nature of polymers to aid in the understanding of ultrathin polymer film wettability. Experimentation that assesses variables known to impact the cooperative motion of polymers, such as bulky side groups [91] or fragility, [93,94] would be insightful to determine if the unexplained changes in contact angle and surface energy presented within are truly driven by cooperativity.…”
Section: Cooperative Nature Of Polymers As a Possible Explanation For...supporting
confidence: 60%
See 4 more Smart Citations
“…[74] It is also reported that T g -confinement effects are pronounced in crosslinked systems when compared to analogous linear polymers. [92] These pronounced effects in the crosslinked system support the large critical thicknesses for contact angle dependence on crosslinked ultrathin PS/PMMA films observed by Petek et al [36] This review invites future work to combine the additive vdW potential with the cooperative nature of polymers to aid in the understanding of ultrathin polymer film wettability. Experimentation that assesses variables known to impact the cooperative motion of polymers, such as bulky side groups [91] or fragility, [93,94] would be insightful to determine if the unexplained changes in contact angle and surface energy presented within are truly driven by cooperativity.…”
Section: Cooperative Nature Of Polymers As a Possible Explanation For...supporting
confidence: 60%
“…[85] We suspect that this temperature difference can also cause conflicting trends in the thickness dependence of surface energy. For example (Figure 8a), PS films spun on Si wafers (Si/SiO x /PS) investigated with surface capillary spectra at 110 °C exhibited decreasing surface energy, [62] while the same system showed multiple reports of increasing surface energy with a decrease in film thickness [29,34,36] when the surface energy is calculated from the contact angle measurements conducted at room temperature. In addition, the thickness-dependence of surface energy is different depending on temperature, even though all data were collected above T g (Figure 3b).…”
Section: Temperature Dependence Of Surface Energymentioning
confidence: 99%
See 3 more Smart Citations